Implications of Cognitive Learning Theory in ICT Education - Diyal, Suresh Bahadur; Malla, Vijaya (Educational Journal, 2025)
This study examines how Cognitivist Learning Theory can be effectively applied in ICT education through the use of digital tools. While cognitivism emphasizes internal mental processes like attention, memory, and metacognition, its integration into technology-enhanced pedagogy, especially in developing contexts, remains underexplored. This mixed-method study utilized survey data from 65 ICT teachers, interviews with 12 instructors, and classroom observations in 10 Nepalese tertiary institutions. Data analysis focused on cognitivist principles such as schema activation, cognitive load management, metacognition, and learner motivation. Findings reveal that ICT tools, when aligned with cognitive principles, act as effective cognitive scaffolds. Teachers reported using multimedia, simulations, adaptive quizzes, gamified dashboards, and reflection journals to activate prior knowledge, manage cognitive load, and foster self-regulated learning. Observations confirmed improved conceptual organization, sustained attention, and learner persistence, though risks of cognitive overload from excessive multimedia were noted. The study identifies personalization, scaffolding, and timely feedback as crucial for strengthening cognitive engagement. This research contributes an implementation model and practical insights for integrating cognitivism into digital pedagogy, transforming ICT from a passive medium into an active enabler of deep learning.